Hexapod coloron at the LHC - Yang Bai; Sida Lu; Qian-Fei Xiang (Journal of High Energy Physics, 2018)
Abstract Instead of the usual dijet decay, the coloron may mainly decay into its own “Higgs bosons”, which subsequently decay into many jets. This is a general feature of the renormalizable coloron model, where the corresponding “Higgs bosons” are a color-octet Θ and a color-singlet ϕ I . In this paper, we perform a detailed collider study for the signature of pp→G′→Θ→ggϕI→ggqq¯ $$ pp→ G^{′}→ \left(\varTheta\ → gg\right)\left(φ_I→ ggq\overline{q}\right) $$ with the coloron G ′ as a six-jet resonance. For a light ϕ I below around 0.5 TeV, it may be boosted and behave as a four-prong fat jet. We also develop a jet-substructure-based search strategy to cover this boosted ϕ I case. Independent of whether ϕ I is boosted or not, the 13 TeV LHC with 100 fb−1 has great discovery potential for a coloron with the mass sensitivity up to 5 TeV.